KARAKTERISTIK SLUDGE BIOGAS SEBAGAI PUPUK ORGANIK - Novilda Elizabeth Mustamu (JURNAL AGROPLASMA, 2019)
Sludge biogas is the waste of processing biogas which can use as organic fertilizer. The Objectives were to study a characteristic of sludge biogas as organic fertilizer. The experiment was conducted in Hutapaung Village, Humbang Hasudutan and the sample was analized in Socfindo Laboratory and National Standard Foundation Laboratory, from March 2016 until April 2016. The data were compared by Quality Standard Organic Fertilzer (SNI) 19-7030-2004 and SNI 01-2897-1992. The result showed that sludge biogas has C/N Ratio 10,32, so it can use as organic fertilizer and the composition of macro nutrition is suitable based on SNI. Keywords : sludge biogas, organic fertilizer, SNI, pathogen bacteria.